Factors associated with pneumococcal vaccine uptake in elderly subjects referred to the respiratory department - Watanabe, Keisuke; Asai, Yoshihito; Tsurikisawa, Naomi; Oshikata, Chiyako; Kaneko, Takeshi (Nagoya journal of medical science, 2020)
Streptococcus pneumoniae is the most common pathogen for community-acquired pneumonia and is also common in nursing and healthcare-associated pneumonia. Pneumococcal vaccine shows clinical benefit and 23-valent pneumococcal polysaccharide vaccine (PPSV23) has been introduced in a routine immunization program in Japan. However, uptake of PPSV23 remains low, at 40%. One opportunity for capturing unvaccinated subjects is hospital referrals. Identifying factors associated with pneumococcal vaccination among referred subjects is thus important so that pulmonologists can maximize the capture of unvaccinated subjects. We retrospectively reviewed the records of subjects with a first referral to the Department of Respiratory Medicine at Hiratsuka City Hospital from September 2017 to March 2018. Subjects who were ≥65 years old and lived in Hiratsuka were included in this study. We compared the backgrounds of subjects and investigated factors associated with pneumococcal vaccination. A total of 142 individuals were included in this study and the pneumococcal vaccination rate was 44.4% (95% confidence interval (CI), 36.0–52.9%). Of these, 127 subjects regularly visited clinics and/or hospitals for any diseases and their pneumococcal vaccine rate was 44.1% (95%CI, 35.3–53.2%). In multivariate analysis, chronic respiratory diseases (odds ratio 5.7; 95%CI, 2.2–14.9, P<0.001) and receipt of PPSV23 notification (odds ratio 8.5; 95%CI, 2.5–29.0, P<0.001) were positively associated with pneumococcal vaccination. In conclusion, chronic respiratory diseases and receipt of PPSV23 notification were positively associated with pneumococcal vaccination. However, pneumococcal vaccination rates remain relatively low, even in subjects regularly visiting clinics and/or hospitals.